Every other integer is odd, so to get the next odd integer, you add 2 to the current integer:
(2n + 1) + 2 = 2n + 3
2006-12-28 08:17:01
·
answer #1
·
answered by Jim Burnell 6
·
2⤊
0⤋
I'm going to fill in some numbers for n:
2(1)+1=3
2(2)+1=5
2(3)+1=6
2(4)+1=9
2(5)+1=11
Any number filled in for n comes out odd. For 2n+1 any number filled in would be an odd integer, so If you add one more to the equation 2n+1+1 or 2n+2, then you would get all even numbers:
2(1)+2=4
2(2)+2=6
2(3)+2=8
2(4)+2=10
2(5)+2=12
So you gotta make it 2n+3 which is 2n+1+1+1:
2(1)+3=5
2(2)+3=7
2(3)+3=9
2(4)+3=11
2(5)+3=13
And it's simple enough a child could understand it now right?
2006-12-28 16:25:02
·
answer #2
·
answered by Jade 2
·
0⤊
0⤋
It's simple; since odd numbers go
1, 3, 5, 7, 9, 11, 13, ....
Notice that they differ by 2 every time. That means if
2n + 1 represents an odd integer, the next odd integer would be 2 more; i.e.
(2n + 1) + 2
Which is equal to
2n + 3
2006-12-28 16:18:37
·
answer #3
·
answered by Puggy 7
·
0⤊
0⤋
Replace n by n+1 to get 2(n+1) + 1 = 2n+3.
2006-12-28 16:18:41
·
answer #4
·
answered by steiner1745 7
·
0⤊
0⤋
Odd integers are separated by 2 ==> if X is the Yth odd integer, then (X+2) is the (Y+1)th odd integer ==> if (2N+1) is the Yth odd integer, then (2N+1) + 2 = 2N+3 is the next odd integer.
2N+3
2006-12-28 16:17:26
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
2n + 3 represents the next odd integer because to get to the next odd number, all you need to add is 2.
2006-12-28 16:17:42
·
answer #6
·
answered by blue.moon 2
·
0⤊
0⤋
(2n+1)+2
so
2n+3
2006-12-28 16:18:15
·
answer #7
·
answered by L_Bizzy25 2
·
0⤊
0⤋
2n+1
2= n-1
2+1=n
n=3
So, it is 2n+3
2006-12-28 16:24:23
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
(2n + 1) , (2n + 3)
2006-12-28 18:28:29
·
answer #9
·
answered by aeiou 7
·
0⤊
0⤋